Nano-fertilizers: Bio-fabrication, application and biosafety - Rabaa Yaseen; Ahmed I. S. Ahmed; Amal M. Omer; Mohamed K. M. Agha; Tamer M. Emam (Novel Research in Microbiology Journal, 2020)
At the global level, sustainable horticulture faces many challenges due to climate changes in addition to limitations in water and land resources. Nanotechnology is an innovate strategy for sustainable agricultural development. This eco-friendly technology is becoming vital in modern agricultural practices, due to its role in improving plants production, protection with environmental security, biological supportability and financial steadiness. Production of nano-fertilizers is considered as the most important alternative to the conventional fertilizers and pesticides, due to their potential roles in crop production, reducing the use of chemical fertilizers and mitigating the adverse impacts in soil. The aims of the current study were to highlight nanotechnology in terms of several important definitions including; nano-fertilization, biosynthesis of nano-fertilizers and the use of nanomaterial as an alternative to the traditional mineral fertilizers. This is in addition to the control of nutrient release in the soil, nanoparticles (NPs) role in enhancing the bio-agent activity, and the fate of nanomaterials in plants with respect to the toxicological data of any nano-product.